A pilot study of intrahepatic yttrium‐90 microsphere radioembolization in combination with intravenous cisplatin for uveal melanoma liver‐only metastases. Issue 4 (14th May 2019) - Arulananda, Surein; Parakh, Sagun; Palmer, Jodie; Goodwin, Mark; Andrews, Miles C.; Cebon, Jonathan
Abstract: Background: Metastatic uveal melanoma is a highly aggressive disease with no standard of care treatment option. A large proportion of patients have liver‐only metastatic disease which raises the question if liver‐directed therapy can be efficacious in this subpopulation. Aims: The study aims to evaluate the safety and efficacy of radiosensitizing chemotherapy in combination with yttrium‐90 microspheres in patients with uveal melanoma with liver‐only metastases. Methods and results: This single arm, open labeled, non‐randomized study enrolled 10 patients with liver‐only metastatic uveal melanoma between November 2012 and January 2018. Eligible patients received intrahepatic yttrium‐90 microspheres followed by intravenous cisplatin (20 mg/m 2 ) for 5 days. Ten patients were enrolled, but nine patients received treatment who were included in the final analysis with a median follow‐up of 30 months (range 7 to 44). Five (50%) were female, five (50%) had an elevated lactate dehydrogenase (LDH), and one (10%) had prior anti‐PD‐1 therapy. The combination was well tolerated with no greater than or equal to grade 3 toxicity observed. The liver objective response rate (ORR) was 33% (3/9), the median progression‐free survival (PFS) in the liver was 3 months (95% CI, 3‐NA), and the extrahepatic PFS was 3 months (95% CI, 3‐NA). Seventy‐eight percent (7/9) received an immune checkpoint inhibitor on disease progression, with no responses seen. The median overall survival (OS) was 10 months (95% CI, 7‐NA). Conclusion: The combination of cisplatin with yttrium‐90 microspheres was well tolerated; however, it was associated with intrahepatic disease control of relatively short duration. No responses were seen in patients treated with immune checkpoint inhibitors post radioembolization.